A review of Japanese species of Allophrys Förster (Hymenoptera: Ichneumonidae: Tersilochinae) - Khalaim, Andrey I. (Zootaxa, 2017)
Three species of the genus Allophrys Förster are found to occur in Japan: A. matsumurai sp. nov., A. takemotoi sp. nov. and a third morphospecies known only from males. This is the first description of Allophrys species from Japan, as well as from the entire Palaearctic region. An identification key to Japanese species of Allophrys is provided.